Emulsifiers in diets with energy reduction for laying hens - Oliveira, Marllon José Karpeggiane de; Geraldo, Adriano; Lemke, Sara Santana Ramos; Valentim, Jean kaique; Fassani, Édison José; Carvalho, Jordanna Barbosa Ferreira De; Miranda, Diogo Alvarenga; Silva, Eliane Aparecida (Acta Scientiarum. Animal Sciences, 2022)
Emulsifiers in animal diets are an interesting and effective strategy for nutritionists to improve the digestion of dietary lipids and, consequently, provide better performance. This study aimed to evaluate the effect of the supplementation of diets with emulsifier based on mono- and diglycerides (120 g t-1 of feed) associated with different energy levels (2,775; 2,725; 2,675 and 2,625 kcal of metabolizable energy kg-1 of feed) on performance and egg quality of Hisex Brown laying hens. The laying hens were distributed in 50 experimental plots with eight birds each. A completely randomized design with five treatments and ten replicates/treatments was used. The treatments in this study were: control diet (C) with 2,775 kcal of metabolizable energy (ME) kg-1 of feed; C + E: diet C supplemented with an emulsifier (E) at 120 g t-1 of feed; diet C with reduction of 50 kcal ME and supplemented with E (NC50 + E); diet C with reduction of 100 kcal ME and supplemented with E (NC100 + E); and diet C with reduction of 150 kcal ME and supplemented with E (NC150 + E). All diets had the same inclusion level of degummed soybean oil (2%). There was no influence of the treatments on the performance and quality of the eggs (p >0.05). The current study has shown that diets supplemented with emulsifiers based on mono- and diglycerides (120 g t-1) allows reducing the metabolizable energy level up to 150 kcal kg-1 of feed, without impairment on performance and egg quality of Hisex Brown laying hens